Effect of drying processes on the final quality of potimarron pumpkin (Cucurbita maxima) powders. Issue 1 (22nd December 2021) - Benseddik, Abdelouahab; Benahmed-Djilali, Adiba; Azzi, Ahmed; Zidoune, Mohammed Nasreddine; Bensaha, Hocine; Lalmi, Djemouai; Allaf, Karim
Abstract: This research work focuses on a comparative study of the impact of four drying processes (Air Flow Drying (AFD), Freeze-Drying (FD), Vacuum Multi Flash Drying (VMFD), and Swell-Drying (SD) coupling Instant Controlled Pressure-drop (DIC) to standard Air Flow) on the biochemical, physicochemical, thermochemical, and biological properties of the pumpkin potimarron ( Cucurbita maxima ) powders. The main results showed that the availability of bioactive substances was much more related to the drying process and attributed to the porosity. VMFD, SD, and FD drying processes had the best preservation of Total Polyphenols (TPP) and Total Flavonoids (TF) much better than AFD. It is worth noting that FD and SD improve the availability thanks to the presence of multi-particulate pores, while VMFD keeps better preservation of thermo-sensitive products. Graphical Abstract: UF0001